Cycle Tests and Structure Repair of Bridge Pier Models: Uji Siklus dan Perbaikan Struktur Model Pilar Jembatan - Justitiannisa, Innino; Gunadi, Riawan (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
This research was conducted in anticipation of the risk of fatal damage to the structure due to the earthquake. In this study, experiments were carried out on the test object in the form of a bridge pillar model, which consisted of 2 test steps. The cyclic test is in the form of a pier bridge model and is continued in step 2 in the form of repairs with grouting and carbon wrapping materials as well as conducting another cyclic test to evaluate the performance of the repair materials used. This study uses the pier model, which consists of two test objects, namely a column with dimensions of 0.25x0.25x1.68 meters and a column cap of 1.20x0.55x0.36 meters. This test provides a constant axial load of 0.2 fc’.Ag and a cyclic lateral load. Phase 1 testing was carried out until the drift ratio was 3.5%. The achieved lateral peak strength is 8,606 tonf with a drift ratio of 2.20%. Lateral strength experienced a decrease in peak lateral strength of 86.93%. The damage is dominated by shear cracks which are characterized by the number of cracks with a diagonal pattern. Structural performance analysis was carried out according to ACI 374.1-05. The results of the theoretical analysis of the peak strength of the pier model were 15.2144 tonnes in the tensile direction, while the experimental ones were 8.606 in the pushing direction and -7.812 in the pulling direction.